Digitalization of Classrooms: A Comparative Study on Teachers’ Perceptions about the Use of Digital Teaching Materials in Early Childhood and Primary Education - María Isabel Vidal-Esteve; Sebastián Martín-Gómez (Education Sciences, 2023)
The incorporation of digital didactic materials into the teaching and learning process of students, both in Early Childhood and Primary Education, inevitably entails changes. Some of them concern teacher training, others the interactions and roles of the members of the educational community, and others the innovation, a priori, of the educational process itself. In this context, characterized by the digitization of classrooms, questions arise that this research aims to answer: What vision do teachers have of the incorporation of these media? In what learning situations are they used and for what purposes? Are there differences between the use of digital resources in the infant and primary school stages? This article aims to analyze and compare the perceptions of teachers in two different contexts: the Autonomous Community of the Canary Islands and the Valencian Community. By means of a qualitative study, the focus is on knowing the teachers’ assessment of the usefulness of these resources and on identifying the uses given to them in classroom practices. The results show how, despite the widespread use of digital materials in both stages, some teachers are rethinking their use with students at an early age.